Hypoxia: a Review - Gilany, Kambiz; Vafakhah, Mohtaram (Archives of Advances in Biosciences, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; p.MsoNoSpacing, li.MsoNoSpacing, div.MsoNoSpacing mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; mso-style-link:"No Spacing Char"; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:Arial; span.NoSpacingChar mso-style-name:"No Spacing Char"; mso-style-unhide:no; mso-style-locked:yes; mso-style-link:"No Spacing"; mso-ansi-font-size:11.0pt; mso-bidi-font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-hansi-font-family:Calibri; mso-bidi-font-family:Arial; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Tissue hypoxia occurs where there is an imbalance between oxygen supply and consumption. Growing evidence from experimental and clinical studies points to the fundamental and patho-physiologic role of hypoxia in cancer, ischemic tolerance, and stroke. Hypoxia-induced changes in ion homeostasis, erythropoiesis, angiogenesis, proliferation and differentiation. This review outlines hypoxia effect at molecular level and describes briefly hypoxia role in the physiological and pathological conditions.